A Strategic Framework to Use Payback Period (PBP) in Evaluating the Capital Budgeting in Energy and Oil and Gas Sectors in Oman - Al Ani, Mawih Kareem (International Journal of Economics and Financial Issues, 2015)
This study aims to examine the associations between strategic variables and use the PBP in evaluating the capital budgeting decisions from the perspective of managers and investors in Oman. These variables are risk, liquidity, profitability, market obstacles, management compensation and size of the company. The two samples are investors and managers where 57 out of 65 managers and 57 out of 75 investors were selected to answer the questionnaire of the study. The questionnaire consisted of seven sections with 17 questions. The regression test showed that the risk and management compensation variables have an impact on the use of PBP from the perspective of managers. Also, the risk and profitability variables have an impact on the use of PBP from the perspective of investors. On the second level of analysis, the finding of the study indicates that there are no statistically differences between managers and investors to use the PBP traced to the any of the six variables. Keywords: Strategic Variables; Capital Budgeting; Payback Period (PBP) JEL Classifications: G31; M40; M41